2009
DOI: 10.1111/j.1461-0248.2009.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Shrub encroachment can reverse desertification in semi‐arid Mediterranean grasslands

Abstract: The worldwide phenomenon of shrub encroachment in grass-dominated dryland ecosystems is commonly associated with desertification. Studies of the purported desertification effects associated with shrub encroachment are often restricted to relatively few study areas, and document a narrow range of possible impacts upon biota and ecosystem processes. We conducted a study in degraded Mediterranean grasslands dominated by Stipa tenacissima to simultaneously evaluate the effects of shrub encroachment on the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
277
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(307 citation statements)
references
References 54 publications
11
277
0
9
Order By: Relevance
“…These processes will likely have cascading effects on other biota and on ecosystem functioning [93,97,98]. As an example, a recent survey of global drylands has shown that plant species richness is positively linked to ecosystem multifunctionality, which is also negatively related to annual mean temperature [19].…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes will likely have cascading effects on other biota and on ecosystem functioning [93,97,98]. As an example, a recent survey of global drylands has shown that plant species richness is positively linked to ecosystem multifunctionality, which is also negatively related to annual mean temperature [19].…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
“…the expansion of woody vegetation into former grasslands [99]), a key land-cover change affecting drylands worldwide, has multiple effects on ecosystem structure and functioning [100]. Although this phenomenon has not been found to significantly affect ecosystem attributes such as biodiversity at the global scale [100], it may either enhance or reduce plant species richness at local and regional scales [97,101]. Some studies have suggested that different global change drivers, such as increases in [CO 2 ] and in the frequency of large precipitation events, may favour shrubs at the expenses of grasses in drylands [49,102,103].…”
Section: Global Environmental Change Effects On Drylandsmentioning
confidence: 99%
“…However, recent studies have indicated that shrub encroachment has positive effects on the ecosystem functions of herbaceous biomass [15], microbe diversity, and nitrogen mineralization [16]. Based on the experiment in southeast Spain [17], shrub encroachment has been found to increase soil organic carbon, total nitrogen, and biological soil crusts. Instead of leading to desertification in previous studies, shrub encroachment is considered to reverse desertification in the Mediterranean grasslands [17].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experiment in southeast Spain [17], shrub encroachment has been found to increase soil organic carbon, total nitrogen, and biological soil crusts. Instead of leading to desertification in previous studies, shrub encroachment is considered to reverse desertification in the Mediterranean grasslands [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the early successional stage, living environments are difficult for plants to survive due to excessive light, lack of water, and scarce nutrient in the soil (García-Orth & Martínz-Ramos 2011). But the vast energy fixing by plants through strong photosynthetic capacity (Navas et al 2010), root growth (Maestre et al 2001(Maestre et al , 2009, and litter decomposition (Wardle et al 1998;Maestre et al 2001) improves the habitat and accelerates the process of plant succession to a certain extent. Grasses can ameliorate the abiotic environment and facilitate the introduction of other species.…”
Section: Introductionmentioning
confidence: 99%